2016
DOI: 10.1111/ecc.12435
|View full text |Cite
|
Sign up to set email alerts
|

The first step in ensuring patient-centred quality of care: ask the patient

Abstract: Health providers may not be aware of their patients' needs or preferences, and patients reluctant to raise their concerns. Consequently, the first step in ensuring quality of care is to ask the patient about the care that they would like. A cross-sectional sample of 244 medical oncology outpatients were surveyed about provider-asking behaviours across six dimensions of patient-centred care defined by the Institute of Medicine. Specifically, were patients asked by clinic staff at the treatment centre about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…The significance of involving family and friends is in line with the findings at the outpatient ORL department and in cancer care worldwide [22, 25, 26]. …”
Section: Discussionmentioning
confidence: 55%
“…The significance of involving family and friends is in line with the findings at the outpatient ORL department and in cancer care worldwide [22, 25, 26]. …”
Section: Discussionmentioning
confidence: 55%
“…For patients with hematological cancers, individualized health communication previously has been suggested to fill knowledge gaps and address provider dissatisfaction caused by miscommunication of patient priorities . For example, research has demonstrated that patients with cancer rarely are asked about their mental health, yet they consider their mental health to be in the poorest state after completing treatment . Additional research questions raised by the current study centered around mental health treatment and resources impacting patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Survivorship is a burgeoning field for oncologists and researchers as factors determining these priorities change. Unfortunately, survivors' emotional and psychological burdens during the cancer experience often are unaddressed because providers rarely emphasize any aspect of patient care other than the patient's physical needs . Examining and addressing these unmet psychosocial needs can improve the overall well‐being of patients and survivors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies have looked at whether patients’ preferences for involvement in decision‐making match their experiences (Tariman et al., ; Vogel, Helmes, & Hasenburg, ). Also, numerous studies have suggested that to provide patient‐centred decision‐making in cancer care, healthcare providers should ask patients about their preferences for involvement in decision‐making regarding their care (Lee et al., ; Zucca et al., ). However, to our knowledge, no study has assessed whether asking patients about their decision‐making preferences is associated with discordance between patients’ preferred and perceived involvement in deciding on their cancer treatment.…”
Section: Introductionmentioning
confidence: 99%